24 frames [videorecording (DVD)] - Kiarostami, Abbas; Kiarostami, Abbas; Kiarostami, Abbas (Criterion collection, 2019)
Filmmaker Abbas Kiarostami recreates the final three years of his life through twenty-four short films inspired by a collection of still images.